In-situ micro-tensile investigation of strain rate response along <100> and <110> directions in single crystal nickel. (July 2018) - Xu, Alan; Saleh, Michael; Davis, Joel; Edwards, Lyndon; Bhattacharyya, Dhriti
Abstract: The effect of crystal orientation and strain rate on the deformation behaviour of high-purity Ni single crystals is investigated using in-situ micro-tensile techniques. Ni foils, 12 μm thick, were fashioned into micro-tensile samples. The samples were pulled in tension along <100> and <110> directions at nominal displacement rates of 5 nm/s and 500 nm/s. These orientations were chosen because of the expectation of multiple slip on different numbers of slip systems. Analysis of stress-strain plots in conjunction with orientation imaging revealed that the <110> oriented samples featured a lower yield stress, higher elongation and more complex deformation behaviour than the <100> oriented sample. In fact, the samples with <110> orientation showed two peaks in the engineering stress-strain curves, a unique behaviour hitherto unobserved. The higher strain rate increased the flow strength for both orientations, the results being in broad agreement with macroscopic tests. These results are analysed using plasticity theory, and it is shown that the results obtained from microscopic tests in single crystal Ni are largely consistent with macro-scale behaviour in polycrystalline samples if the appropriate theoretical adjustments are made for size and orientation effects, using Hall-Petch and Taylor theories. Graphical abstract: Image 1 Highlights: Methodology for accurately preparing and analysing micro-tensile samples. Micro-mechanical testing of Ni single crystals along <100> and <110> crystal directions at different strain rates. The Critical Resolved Shear Stress of Ni was measured and EBSD analysis determined slip systems for <100> and <110> directions. Strain rate effect was observed at a micro-scale. The yield stress and strain rate sensitivity scaled well to bulk macro-scale properties.